Pázsint, A.-I. Prosopographia Ponti Euxini: Callatis et Odessus. Cluj-Napoca 2024. Editura Mega, 308 pages. ISBN: 978-606-020-707-8 - Çilingir, İbrahim Melih (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
This review presents Annamária-Izabella Pázsint’s Prosopographia Ponti Euxini: Callatis et Odessus as a methodologically rigorous and highly valuable prosopographical study that reconstructs the social structures, mobility patterns, and civic hierarchies of Callatis and Odessus through a systematic analysis of literary and especially epigraphic evidence.